2020
DOI: 10.7324/japs.2021.110701
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infections: Virulence factors, resistance to antibiotics, and management of uropathogenic bacteria with medicinal plants—A review

Abstract: Urinary tract infections (UTIs) are among the most common infections in most countries and they are usually caused by the so-called uropathogenic (UP) microorganisms, including Escherichia coli (80%-90%), Staphylococcus aureus, Enterococcus faecalis, Pseudomonas aeruginosa, Proteus mirabilis, and Klebsiella pneumoniae. Over the years, the growth of resistance to antibiotics has complicated the treatment of UTIs and has direct consequences on the cost of treatment, the severity of infections, and the length of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 77 publications
(35 reference statements)
1
14
1
Order By: Relevance
“…The absence of antimicrobial activity of the ethanolic extract of C. citratus observed in this study is also in disagreement with several other studies that have also investigated the antibacterial effect of lemongrass [75][76][77][78]. This difference between the results of the present study and those observed in others could be explained by several factors, such as the geographical area of origin of the extracted plants [79], the extraction procedure [80][81][82], and the phenotype and genotypic differences of the strains tested [83]. De Sá Filho et al [79] recently reported that factors such as the physicochemical characteristics of soils, different dynamics of the action of climatic factors, and the consequent diversity of biological interactions in biomes greatly affect the chemical composition of plants.…”
Section: Inhibition Zone (Iz)contrasting
confidence: 99%
See 1 more Smart Citation
“…The absence of antimicrobial activity of the ethanolic extract of C. citratus observed in this study is also in disagreement with several other studies that have also investigated the antibacterial effect of lemongrass [75][76][77][78]. This difference between the results of the present study and those observed in others could be explained by several factors, such as the geographical area of origin of the extracted plants [79], the extraction procedure [80][81][82], and the phenotype and genotypic differences of the strains tested [83]. De Sá Filho et al [79] recently reported that factors such as the physicochemical characteristics of soils, different dynamics of the action of climatic factors, and the consequent diversity of biological interactions in biomes greatly affect the chemical composition of plants.…”
Section: Inhibition Zone (Iz)contrasting
confidence: 99%
“…De Sá Filho et al [79] recently reported that factors such as the physicochemical characteristics of soils, different dynamics of the action of climatic factors, and the consequent diversity of biological interactions in biomes greatly affect the chemical composition of plants. In addition, the previous studies have revealed that the types of extraction, the extraction parameters such as the nature of solvents used and their concentration, the m/v ratio, the temperature, and the extraction time can lead to very significant differences in the chemical composition of the extracts and therefore of the antimicrobial activity [80,81]. In a recent study, genotypic and phenotypic differences between microorganisms of the same species can induce changes in susceptibility to existing antibiotics or antimicrobials [81].…”
Section: Inhibition Zone (Iz)mentioning
confidence: 99%
“…This phenomenon is particularly observed in Gram-negative bacteria because of their ability to easily accumulate resistance genes and the presence of efflux pumps in their membranes, which are used to expel antimicrobials from the cells. This capability makes these bacteria unresponsive or resistant to various types of antibiotics [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the use of antibiotics in animal husbandry is not limited to therapeutic purposes but is mostly used for prophylactic purposes and as growth promoters to achieve high return in protein (Dipeolu and Alonge, 2002). Antibiotics have been used for treating bacterial infections in both humans and animals; however, their application in animals has doubled in recent years (Aarestrup, 2012;Bacanl and Başaran, 2019;Arsene et al, 2021). In a particular report, the global consumption of antibiotics in livestock farming is reported to be over 80% and mostly not for therapeutic purposes (Boeckel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%